Critical Factors Influencing Human Resource Training Effectiveness in Pakistan's Higher Educational Sector - Ifrah, Laiq (2024)
In the era of rapid technological advancement, organizations increasingly adopt new technologies, underscoring the need for skilled human resources. The quality of education in higher education institutions heavily relies on the qualifications and abilities of human resource staff, making their learning and development a critical priority. Despite significant investments in human resource training, valuation of these programs is often lacking, limiting the ability to assess their effectiveness. This research valuates training effectiveness using first two levels of Kirkpatrick’s model of training evaluation (1959) and identifies key factors the model overlooks, particularly in the Asian context. The study focuses on the influence of training and individual factors on outcomes like reaction and learning and examines the moderating role of organizational and work environment factors. The study used a quantitative, cross-sectional survey approach with a positivist philosophy and applied a stratified random sampling approach to ensure equal gender representation. A quantitative survey of 655 trainees of Human Resource Capacity Building Program, analyzed using SPSS for descriptive statistics and exploratory factor analysis, and AMOS for structural equation modelling, revealed that training factors significantly impact reaction outcomes, while individual factors are more critical for learning outcomes. Organizational and work environment factors partially moderate the relationship between individual factors and training effectiveness. The findings provide valuable insights for HR professionals, training departments, and stakeholders, encouraging them to design training programs that closely mirror job requirements and involve hands-on applications to help trainees apply new skills effectively in the workplace. The study highlights the importance of peer and organizational support in achieving positive training outcomes and calls for further research within Asian organizations that are investing in and anticipating positive results from their training programs, despite its methodological limitations and scope constraints.